Radiolabel validation of cortisol in the hair of rhesus monkeys. (November 2018) - Kapoor, Amita; Schultz-Darken, Nancy; Ziegler, Toni E.
Highlights: Systemically administered [ 3 H]-cortisol was detected in the hair as cortisol. Demonstrated for that hair cortisol is representative of circulating cortisol. [ 3 H]-cortisol was incorporated into hair as cortisone. [ 3 H]-cortisol was also incorporated into hair as other unknown cortisol metabolites. Abstract: Analysis of cortisol in hair has become a widespread tool for assessment of hypothalamic-pituitary-adrenal (HPA) axis activity because of its ease of collection and its ability to provide cumulative data over a period of months. In order to meaningfully interpret hair cortisol, however a direct validation by radio-metabolism is required to understand cortisol incorporation into hair. Tritiated [ 3 H]-cortisol was IV administered to adult rhesus monkeys to determine 1) if [ 3 H] is found in the hair after injection of [ 3 H]-cortisol, 2) the growth rate of hair and 3) the form in which cortisol is found in hair. Samples of hair were collected from newly and previously shaved patches at 14-days and 28-days after [ 3 H]-cortisol injection. Hair was processed by external wash, grinding, and hormone extractions. Samples were separated by high-performance liquid chromatography (HPLC) and fractions were collected and radioactivity assessed. We found [ 3 H] incorporated into the hair by the 14-day hair collection and no new radioactivity was found by the 28-day collection. Individual hair growth rate was highly variable between monkeys, indicating that the between-subject hair growth patterns were not consistent. Importantly, for the first time, we showed that systemically administered [ 3 H]-cortisol was found in the hair as [ 3 H]-cortisol and [ 3 H]-cortisone, as well as other glucocorticoid metabolites.